Molecular and genetic basis of plant architecture in soybean - Li, Weiwei; Wang, Lei; Xue, Hong; Zhang, Mingming; Song, Huan; Qin, Meng; Dong, Quanzhong (Frontiers in Plant Science, 2024)
Plant architecture determines canopy coverage, photosynthetic efficiency, and ultimately productivity in soybean (Glycine max). Optimizing plant architecture is a major goal of breeders to develop high yield soybean varieties. Over the past few decades, the yield per unit area of soybean has not changed significantly; however, rice and wheat breeders have succeeded in achieving high yields by generating semidwarf varieties. Semi-dwarf crops have the potential to ensure yield stability in highdensity planting environments because they can significantly improve responses to fertilizer input, lodging resistance, and enhance resistance to various abiotic and biotic stresses. Soybean has a unique plant architecture, with leaves, inflorescences, and pods growing at each node; internode number greatly affects the final yield.Therefore, producing high-yielding soybean plants with an ideal architecture requires the coordination of effective node formation, effective internode formation, and branching. Dozens of quantitative trait loci (QTLs) controlling plant architecture have been identified in soybean, but only a few genes that control this trait have been cloned and characterized. Here, we review recent progress in understanding the genetic basis of soybean plant architecture. We provide our views and perspectives on how to breed new high-yielding soybean varieties.